2022
DOI: 10.1038/s41467-022-29816-1
|View full text |Cite
|
Sign up to set email alerts
|

Installation of synergistic binding sites onto porous organic polymers for efficient removal of perfluorooctanoic acid

Abstract: Herein, we report a strategy to construct highly efficient perfluorooctanoic acid (PFOA) adsorbents by installing synergistic electrostatic/hydrophobic sites onto porous organic polymers (POPs). The constructed model material of PAF-1-NDMB (NDMB = N,N-dimethyl-butylamine) demonstrates an exceptionally high PFOA uptake capacity over 2000 mg g−1, which is 14.8 times enhancement compared with its parent material of PAF-1. And it is 32.0 and 24.1 times higher than benchmark materials of DFB-CDP (β-cyclodextrin (β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 61 publications
(91 reference statements)
3
47
0
Order By: Relevance
“…The intriguing features of MOFs lie primarily in their great promise for various applications as well as unprecedented, rich chemistry. The potential applications of MOFs have spread from gas storage/separation, catalysis, , to food preservation, , and environmental protection. Endeavors are being made for the industrial implementation of MOFs in related fields . On the other hand, the structure diversity, framework flexibility, tunable pore structure, and functionality of MOFs have brought exciting chemistry findings. , …”
Section: Introductionmentioning
confidence: 99%
“…The intriguing features of MOFs lie primarily in their great promise for various applications as well as unprecedented, rich chemistry. The potential applications of MOFs have spread from gas storage/separation, catalysis, , to food preservation, , and environmental protection. Endeavors are being made for the industrial implementation of MOFs in related fields . On the other hand, the structure diversity, framework flexibility, tunable pore structure, and functionality of MOFs have brought exciting chemistry findings. , …”
Section: Introductionmentioning
confidence: 99%
“…Both adsorbents exhibited fast adsorption kinetics common for adsorption processes facilitated by electrostatic interactions, with the maximum adsorption achieved in less than 1 h. While this treatment time is promising for efficient PFOA removal, POPs have been reported that can achieve 99.99% removal in 2 min. 46 Nonetheless, our synthesis is advantageous as it can facilitate future performance improvements through surface tuning. PFOA adsorption via both POPs showed pseudosecond-order kinetics (SI, eq 6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[ 4 ] Distinct from traditional polymers, covalent organic frameworks (COFs) are a class of crystalline porous polymer with ordered networks and inherent pores. [ 9–11 ] Despite fascinating features of low density, broad diversity, and high designability, [ 12–19 ] the potential of COFs for low‐frequency electromagnetic wave absorption is unprecedented.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Such materials need to eliminate surface reflection, allow a full entry of low-frequency electromagnetic wave, and dissipate wave energies in their thin films or coatings via magnetic, dielectric, and conductive loss. [1][2][3][4][5] Magnetic loss is based on ferromagnetic materials such designability, [12][13][14][15][16][17][18][19] the potential of COFs for low-frequency electromagnetic wave absorption is unprecedented.…”
Section: Introductionmentioning
confidence: 99%